Difundimos nuestras propuestas para disminuir la vulnerabilidad ante el fenmeno El Nio Costero en el distrito El Porvenir - Castaeda Corrales, Denisse Yamil (2022)
The objective of this professional proficiency work is to propose a learning session in the Social Sciences area aimed at developing the "Responsibly manage the space and the environment" competence through the performance that consists of the students of the thirdgrade of secondary school IEP "Santa Rita de Jess" explain how the decisions of social actorsinfluence vulnerability to disaster risk and propose actionsto prevent thisrisk. To thisend, a series of activities have been planned around the theme of the "El Nio" phenomenonthat occurred at the beginning of the year 2017, also taking into account the transversal approach of the search for excellence. Likewise, it is sought that students monitor and makethe necessary adjustments to improve their academic performance during class and thus manage their learning autonomously. In accordance with the above, a rubric was designed as an evaluation instrument and a "Student self-monitoring sheet" that will allow metacognition in students.